Liposuction for Submental Lymphedema Improves Appearance and Self‐Perception in the Head and Neck Cancer Patient. (8th April 2014) - Brake, Maria K.; Jain, Lauren; Hart, Robert D.; Trites, Jonathan R. B.; Rigby, Matthew; Taylor, S. Mark
Abstract : Objective: Patients who have undergone treatment for head and neck cancer are at risk for neck lymphedema, which can severely affect quality of life. Liposuction has been used successfully for cancer patients who suffer from posttreatment limb lymphedema. The purpose of our study was to review the outcomes of head and neck cancer patients at our center who have undergone submental liposuction for posttreatment lymphedema. Study Design: Prospective cohort study. Setting: Oncology center in tertiary hospital setting. Subjects and Methods: Head and neck cancer patients who underwent submental liposuction for posttreatment lymphedema were included. Nine patients met the study criteria. Patients completed 2 surveys (Modified Blepharoplasty Outcome Evaluation and the validated Derriford Appearance Scale) pre‐ and postoperatively to assess satisfaction. Patients' pre‐ and postoperative photos were graded by independent observers to assess outcomes objectively. Results: Our study demonstrated a statistically significant improvement in patients' self‐perception of appearance and statistically significant objective scoring of appearance following submental liposuction. Conclusion: Submental liposuction improves the appearance and quality of life for head and neck cancer patients suffering from posttreatment lymphedema by way of improving their self‐perception and self‐confidence.